Motivation and Employee Performance: A Case of Commercial Banks - Tamang, Dilip; Karki, Jagadish (Journal of Kapan Multiple Campus, 2025)
Motivation is the process of initiating conscious, purposeful action. It is an internal drive that arouses the interest and readiness of the individuals towards a particular goal, where there was previously little attention to that goal. Moreover, motivation catalyzes employees' work performance. There is a strong relationship between motivation and employee performance. The employees are always directly influenced by motivation to maintain a quality of life and satisfy their needs and social expectations. The recognition of employee motivational factors in advance is the key success of any organization. So, motivation is a hygiene factor that includes company policy, interpersonal relations, salary, job satisfaction, and many other incentives of economic and social well-being. Removing such factors will lead to employee dissatisfaction in any organization. This article is based on the factors that directly affect the employee's motivation. It seeks to answer how different variables are related to the motivation, and what the impacts are on the employee's motivation that directly impact their performance in commercial banks.